2016
DOI: 10.1186/s12939-016-0406-9
|View full text |Cite
|
Sign up to set email alerts
|

Medical security and catastrophic health expenditures among households containing persons with disabilities in Korea: a longitudinal population-based study

Abstract: BackgroundAlthough persons with disabilities need access to comprehensive and consistent healthcare services, a significant number of the poor with disabilities do not receive Medical-Aid due to the conditions of eligibility. We aimed to compare the financial burden of healthcare services between two groups of poor persons with disabilities: those not enrolled in Medical-Aid and Medical-Aid enrollees.MethodsThis study used the 1st–8th data (2008–2014 year) of Panel Survey of Employment for the Disabled (PSED) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 20 publications
1
24
0
Order By: Relevance
“…Even in countries where cash benefits exist for the provision of informal care, such as in Germany, France and Sweden [94], any information about the benefit amounts or co-payments are not provided. The most approximate studies are focused on health expenditures for individuals with chronic diseases [35,36] or disabilities [37][38][39]. The literature states that the annual OOP health care payments (including emergency, inpatient, outpatient and prescription drugs payments) for households with disabled members (those who most need LTC) is $1465 US or 1.29 times higher than households without disabled members.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even in countries where cash benefits exist for the provision of informal care, such as in Germany, France and Sweden [94], any information about the benefit amounts or co-payments are not provided. The most approximate studies are focused on health expenditures for individuals with chronic diseases [35,36] or disabilities [37][38][39]. The literature states that the annual OOP health care payments (including emergency, inpatient, outpatient and prescription drugs payments) for households with disabled members (those who most need LTC) is $1465 US or 1.29 times higher than households without disabled members.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are also studies from Latin America [31] and Brazil [32], as well as two recent studies conducted in Portugal [33] and Greece [34]. OOP payments have also been studied for specific subsamples, such as care for the chronically ill [35,36] and disabled persons [37][38][39]. A recent systematic review concluded that when formal fees are introduced, protection against catastrophic health care payments is needed for the most vulnerable groups [40]; however, to our knowledge, no study has focused on payments allocated to long-term care services.…”
Section: Introductionmentioning
confidence: 99%
“…In most studies, disability is significantly related to lower labor participation rates (Kidd, Sloane, and Ferko, 2000;Gannon, 2009;Bound, Schoenbaum, Stinebrickner, and Waidman, 1999;McCauley, 2019), lower employment rates (Baldwin and Johnson, 1994;Jones, 2017;Bown and Freund, 2019), lower education levels (Perri, 1984;Karmel and Nguyen, 2008;Simo Fotso, Solaz, Diene, and Tsafack-Nanfosso, 2018), lower wages (Kidd, Sloane, and Ferko, 2000;Baldwin and Johnson, 1994;Johnson and Lambrinos, 1985;Haveman and Wolfe, 1990;Jones, 2017;Meyer and Mok, 2019), higher medical expenditures (Rice and LaPlante, 1992;Palmer, Groce, Mont, Nguyen, and Mitra, 2015;Choi, Shin, Cho, Kim, and Lee, 2016), and lower economic well-being (Mizunga and Mitra, 2012;Haveman and Wolfe, 1990;Palmer, Groce, Mont, Nguyen, and Mitra, 2015;Meyer and Mok, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, those analyzing the effects of OPP payments or health insurance on LTC are more limited in number although interest in this issue is growing. Some studies have analyzed OOP payments for specific components of health care such as the chronically ill [34,35] and the disabled population [36][37][38]. In addition, a study across the OECD has measured the protection of long-term care and differences between countries.…”
Section: Documented In the Case Of Private Health Insurance Systemsmentioning
confidence: 99%